2010
DOI: 10.5213/inj.2010.14.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Short-term Surgical Outcome of the Transobturator Tape Procedure in Patients with Stress Urinary Incontinence

Abstract: Purpose: The purpose of our study was to evaluate the influence of obesity on clinical characteristics, quality of life (QoL), and outcomes in patients with stress urinary incontinence (SUI) who underwent the transobturator tape (TOT) surgery. Materials and Methods: The medical records of SUI patients who underwent the TOT operation from January 2007 to February 2009 were retrospectively reviewed. Patients with any neurologic diseases that affect the voiding pattern were excluded, and 107 patients were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 18 publications
1
10
0
4
Order By: Relevance
“…15,16 Tchey and colleagues reported that obese patients had a worse grade of SUI, urgency and UUI than non-obese patients. 10 According to Richter and colleauges, a possible mechanism leading to the development of urge or UUI is obesity-induced neurogenic effects on the pelvic floor. 17 Because the obese female population has a high prevalence of SUI, these patients often present for surgical evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Tchey and colleagues reported that obese patients had a worse grade of SUI, urgency and UUI than non-obese patients. 10 According to Richter and colleauges, a possible mechanism leading to the development of urge or UUI is obesity-induced neurogenic effects on the pelvic floor. 17 Because the obese female population has a high prevalence of SUI, these patients often present for surgical evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, midurethral sling (MUS) procedures have been effective with minimal complications in obese patients. [10][11][12] However the influence of obesity on surgical outcomes of TOT procedure is still controversial and the situation is more complicated when it comes to severely obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…Kalbant apie nutukusių ir antsvorio turinčių moterų šlapimo nelaikymo gydymo, atliekant TVT operaciją, rezultatus, dauguma autorių rekomenduoja šį būdą kaip pasirinkimo operaciją esant nutukusioms pacientėms, nors nerado statistiškai reikšmingo rezultatų skirtumo tarp nutukusių ir normalaus svorio moterų gydymo. Tai rodytų, kad KMI dydis neturi reikšmės šlapimo nelaikymo gydymo galutiniams rezultatams, kai implantuojami pošlapliniai raiščiai [20,21,22,23,24]. 2014 m. atlikta operuotų ligonių anketinė apklausa apie šlapimo nelaikymo įtaką kasdieniam gyvenimui ir jo kokybei.…”
Section: įVadasunclassified
“…Plus récemment, Killingsworth rapporte un taux de satisfaction identique à un an d'une mise en place d'un TVT dans une population de 195 femmes dont 65 en surpoids et 62 obèses [39]. Concernant le TOT, Tchey et al ont démontré, sur une série rétrospective de 107 patientes dont 52 femmes avec un IMC supérieur ou égal à 25, que le taux de complications, de récidive et les résul-tats fonctionnels à un an étaient inchangés par rapport à une population de femmes de poids normal [40].…”
Section: Efficacité Du Traitement De L'incontinence Urinaireunclassified
“…sans noter toutefois de majoration des autres complications plus spécifiques de l'intervention [42]. Concernant la voie transobturatrice, le risque de complications per-et postopératoires à un an n'apparaît pas augmenté en cas de surpoids [40].…”
Section: Complications Spécifiques Chez La Femme Obèseunclassified